2016
DOI: 10.1002/cbf.3206
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A regulates Snail‐mediated epithelial‐mesenchymal transition in hemangioma cells

Abstract: Hemangioma (HA) can be exposed to bisphenol A (BPA) through direct skin absorption. Although numerous studies indicated that BPA can trigger the progression of cancers, there is no study concerning the effects of BPA on development of HA. Our present study revealed that nanomolar BPA can significantly increase the in vitro migration and invasion of HA cells via induction of epithelial-mesenchymal transition (EMT), which was evidenced by the upregulation of vimentin and downregulation of E-cadherin. The BPA tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…This was consistent with recent studies that GPER can mediate the proliferative and migration effects of BPA in cancer cells . Other studies also indicated that ERα is also involved in the biological functions of BPA . The family of estrogen‐related receptor (ERR) is suggested to have a very high bind affinity to BPA, whether ERR was involved in BPA‐triggered promotion of LSCC needs further investigations.…”
Section: Discussionsupporting
confidence: 90%
“…This was consistent with recent studies that GPER can mediate the proliferative and migration effects of BPA in cancer cells . Other studies also indicated that ERα is also involved in the biological functions of BPA . The family of estrogen‐related receptor (ERR) is suggested to have a very high bind affinity to BPA, whether ERR was involved in BPA‐triggered promotion of LSCC needs further investigations.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies indicated that BPA can increase the progression of HA via induction of EMT and upregulation of Snail (Zhai et al, 2016). Our present study found that BPS, the "safety" analog of BPA, can trigger the proliferation of HA cells and its cell cycle transition via upregulation of bFGF.…”
Section: Discussionsupporting
confidence: 62%
“…BPS also has a comparable estrogenic activity as BPA (Kuruto-Niwa et al, 2005). It can induce epithelial-mesenchymal transition (EMT) in HA cells via induction of Snail (Zhai et al, 2016). While the potential effects of BPS on the progression of HA are not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research recognized EMT as a crucial event in prostate tissues collected from human BPH patients and rat BPH prostates, respectively. Other reports have also noted that E2 promoted the EMT process in several tissue types . However, the exact effect of E2 on EMT in benign prostatic epithelial cells remains undefined.…”
Section: Discussionmentioning
confidence: 94%